2016
DOI: 10.1371/journal.pone.0157980
|View full text |Cite
|
Sign up to set email alerts
|

Linking Genes and Brain Development of Honeybee Workers: A Whole-Transcriptome Approach

Abstract: Honeybees live in complex societies whose capabilities far exceed those of the sum of their single members. This social synergism is achieved mainly by the worker bees, which form a female caste. The worker bees display diverse collaborative behaviors and engage in different behavioral tasks, which are controlled by the central nervous system (CNS). The development of the worker brain is determined by the female sex and the worker caste determination signal. Here, we report on genes that are controlled by sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Vleurinck et al . () showed that more DEGs and differentially spliced genes (DSGs) were detected in worker and queen pupae brains than worker and drone brains. Our findings indicate that these nutritional differences have a greater impact on gene expression than haplodioploidy in early larval development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vleurinck et al . () showed that more DEGs and differentially spliced genes (DSGs) were detected in worker and queen pupae brains than worker and drone brains. Our findings indicate that these nutritional differences have a greater impact on gene expression than haplodioploidy in early larval development.…”
Section: Discussionmentioning
confidence: 99%
“…Vleurinck et al . () compared gene expression in brains of honeybee males and females and reported that both sex and caste signals are involved in the gene regulation in male and female brains. Similar results have been demonstrated in the fire ant ( Solenopsis invicta ): the gene expression profiles in haploid males are very different from those of diploid females and even diploid males at three developmental time points (Nipitwattanaphon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a transcriptomic approach, Vleurinck et al (2016) detected 1760 differentially expressed genes (DEGs) in the brain tissue of queens and workers at Pdp phase. Of these genes, 902 were upregulated in workers and 858 were upregulated in queens.…”
Section: Honeybee Brain Development D U R I N G T H E P U P a L A N Dmentioning
confidence: 99%
“…Interestingly, almost all of the DEGs (1623) were protein-coding genes, with only 43 being found to transcribe non-coding RNAs. Of the total number of DEGs, approximately 40% appear to be differentially spliced, with most of these being proteincoding genes (Vleurinck et al 2016). Recently, our group also used a genome-wide approach (microarray hybridization) to identify more than 300 DEGs in the brain of queens and workers at the beginning of the pharate-adult stage (Pp), many of them related to neurogenic processes and cell death prevention (unpublished).…”
Section: Honeybee Brain Development D U R I N G T H E P U P a L A N Dmentioning
confidence: 99%
“…We investigated patterns of gene expression within A. mellifera to understand the relationship between gene expression and gene duplication. We obtained A. mellifera RNAseq reads from four different studies that investigated expression differences between A. mellifera female castes (queens and workers), sexes (workers and drones), worker behavioral states (nurses and foragers), and worker tissues (Cameron et al 2013;Jasper et al 2015;Ashby et al 2016;Vleurinck et al 2016). Ashby et al analyzed expression differences between A. mellifera queen, worker, and drone whole body larvae at stage L5 (PRJNA260604).…”
Section: Gene Expression Data and Analysismentioning
confidence: 99%